Multi-Scale Modeling Recapitulates the Effect of Genetic Alterations Associated With Diffuse Large B-Cell Lymphoma in the Germinal Center Dynamics - Merino Tejero, Elena; Mao, Qirong; Lashgari, Danial; García-Valiente, Rodrigo; Robert, Philippe A.; Meyer-Hermann, Michael; Rodríguez Martínez, María; Guikema, Jeroen E. J.; Hoefsloot, Huub H. C.; van Kampen, Antoine H. C. (Frontiers in Systems Biology, 2022)
Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin's lymphoma. It is a germinal center (GC)-derived, aggressive and heterogeneous disease. Several transcription factors (TFs) and signaling pathways that play a central role in the progression of the GC reaction and B-cell differentiation have been shown to play an oncogenic role in DLBCL. B-cell lymphoma 6 (BCL6) is a transcriptional repressor that induces GC B-cell phenotype and blocks PC differentiation. While interferon regulatory factor 4 (IRF4) and B lymphocyte induced maturation protein 1 (BLIMP1), a transcriptional promoter, both mediate PC differentiation and exit from the GC. Computational models are useful alternatives to trial-and-error experimental investigation. Multiscale models (MSMs) have been used to study the role of cellular and molecular mechanisms involved in tumor growth. In this study, we use an existing MSM of plasma cell (PC) differentiation in the GC to simulate eight different models (M1, M2, M3A, M3B, M4, M8, M2M8, M4M8) with several candidate genetic alterations of the BCL6-IRF4-BLIMP1 regulatory network that lead to TF deregulation and could explain the onset of DLBCL and recapitulate the GC dynamics observed in such conditions. We find that models with loss of BLIMP1 function (M4 and M4M8) result in an accumulation of B cells in the GC and a block of PC differentiation and thus correctly recapitulate the observed GC and TF dynamics. Models with constitutive activation of NF-kB pathway alone and in codominance or co-expression with enforced BCL6 expression (M8 and M2M8) result in a decrease of GC B cells and unaltered PC production at early stages of the GC reaction as observed experimentally. Interestingly, we also find that in M8 and M2M8 models, an increase in PC production could happen at later stages of the GC reaction. Nevertheless, models with enforced BCL6 expression (M1 and M2) result in an expansion of GC B cell population and a block in the PC production that was not observed experimentally. Finally, models with loss of IRF4- and BLIMP1-mediated silencing of BCL6 (M3A and M3B) did not affect GC and TF dynamics.